Adjunctive aripiprazole in risperidone-induced hyperprolactinaemia: double-blind, randomised, placebo-controlled trial. Issue 2 (October 2015) - Raghuthaman, G.; Venkateswaran, R.; Krishnadas, R.
Abstract : Background: Hyperprolactinaemia is a troublesome side-effect of treatment with antipsychotics. Aims: This double-blind, placebo-controlled study aimed at examining the effect of adjunctive treatment with 10 mg aripiprazole on prolactin levels and sexual side-effects in patients with schizophrenia symptomatically maintained on risperidone. Method: Thirty patients taking risperidone were enrolled into the trial (CTRI/2012/11/003114). Aripiprazole was administered at a fixed daily dose of 10 mg/day for 8 weeks. Serum prolactin was measured at baseline and at 8 weeks. Hyperprolactinaemia-related problems, psychopathology and side-effects were evaluated every 2 weeks. Results: Prolactin levels decreased by 58% in the aripiprazole group compared with an increase by 22% in the placebo group. Prolactin levels normalised in 46% of patients in the aripiprazole group (number needed to treat, NNT=2). Aripiprazole improved erectile dysfunction in five out of six patients. There were no significant differences in change in psychopathology or side-effects between groups. Conclusions: Adjunctive aripiprazole reduced prolactin levels in those treated with risperidone, with no effect on psychopathology and extrapyramidal symptoms. This is a potential treatment for hyperprolactinaemia observed during treatment with second-generation antipsychotics.